Recording ten-fold larger IKr conductances with automated patch clamping using equimolar Cs+ solutions - Bloothooft, Meye; Verbruggen, Bente; Seibertz, Fitzwilliam; Heyden, Marcel A. G. van der; Voigt, Niels; de Boer, Teun P. (Frontiers in Physiology, 2024)
Background: The rapid delayed rectifier potassium current (IKr) is important for cardiac repolarization and is most often involved in drug-induced arrhythmias. However, accurately measuring this current can be challenging in human-induced pluripotent stem cell (hiPSC)-derived cardiomyocytes because of its small current density. Interestingly, the ion channel conducting IKr, hERG channel, is not only permeable to K+ ions but also to Cs+ ions when present in equimolar concentrations inside and outside of the cell. Methods: In this study, IhERG was measured from Chinese hamster ovary (CHO)-hERG cells and hiPSC-CM using either Cs+ or K+ as the charge carrier. Equimolar Cs+ has been used in the literature in manual patch-clamp experiments, and here, we apply this approach using automated patch-clamp systems. Four different (pre)clinical drugs were tested to compare their effects on Cs+- and K+-based currents. Results: Using equimolar Cs+ solutions gave rise to approximately ten-fold larger hERG conductances. Comparison of Cs+- and K+-mediated currents upon application of dofetilide, desipramine, moxifloxacin, or LUF7244 revealed many similarities in inhibition or activation properties of the drugs studied. Using equimolar Cs+ solutions gave rise to approximately ten-fold larger hERG conductances. In hiPSC-CM, the Cs+-based conductance is larger compared to the known K+-based conductance, and the Cs+ hERG conductance can be inhibited similarly to the K+-based conductance. Conclusion: Using equimolar Cs+ instead of K+ for IhERG measurements in an automated patch-clamp system gives rise to a new method by which, for example, quick scans can be performed on effects of drugs on hERG currents. This application is specifically relevant when such experiments are performed using cells which express small IKr current densities in combination with small membrane capacitances.